KOMUNIKASI PERSUASIF PEMUKA BEDA AGAMA DI KAMPUNG TOLERANSI, KELURAHAN PALEDANG, KOTA BANDUNG - Dermawan, Herman; Hamidah, Nurlaela (Bayani, 2023)
This research explores the dynamics of persuasive communication between religious leaders in Paledang Village, Bandung City. The focus of the research involved religious leaders representing various religions in the subdistrict. The main aim of this research is to understand the persuasive communication strategies used by religious leaders in an effort to build tolerance, openness and cooperation amidst religious diversity. The research method used is a qualitative approach with in-depth interviews as the main instrument for data collection. Research participants were selected purposively to ensure balanced religious representation. Data analysis was carried out through content analysis techniques, enabling the identification of patterns and key findings related to persuasive communication. The research results show that religious leaders in Paledang Village view tolerance as the main foundation of persuasive communication. Tolerance is defined as an open attitude and respect for differences in beliefs, becoming the basis for building understanding and cooperation. Openness is also a crucial approach in establishing interreligious dialogue, where religious leaders create space for the mutually enriching exchange of ideas and views. Shared language is an important tool in building effective persuasive communication. Religious leaders use inclusive language and shared symbolism to create a collective identity that includes all believers. Thus, a common language is not only a means of communication, but also a tool to strengthen solidarity amidst diversity. In addition, collaborative activities such as inter-religious religious events, joint recitations, and joint social activities have proven to be effective strategies in strengthening relations between religious believers. This activity creates an inclusive space that promotes interfaith participation and cooperation. This research contributes to our understanding of persuasive communication as an instrument for building tolerance and cooperation in multicultural societies. The practical implications include the development of a persuasive communication model that can be adopted by religious leaders and similar communities in other places. Thus, it is hoped that this research can provide insight and guidance for managing religious diversity more effectively at the local level.